Evaluation of platelet count, platelet indices and C-reactive protein in culture proven neonatal sepsis in a tertiary care centre - Mrinalini Das; Dorothy Hazowary; Mahibur Rahman; Matiur Rahman (New Indian Journal of OBGYN)
Background: Neonatal sepsis is the most prevalent and significant cause of neonatal morbidity and mortality, requiring prompt diagnosis and treatment. Positive blood culture is the gold standard for diagnosis; the results of which are delayed by 48 hours with only 30-75% positivity rate and a well-equipped laboratory setting is necessary. Emerging studies suggests platelet count and its indices such as plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW) as reliable and affordable indicators obtainable during regular complete blood counts. Aims and objectives: To determine the platelet count and platelet indices in culture positive neonatal sepsis and its correlation with C-reactive protein in a tertiary care centre. Method: It was a hospital based prospective study carried out in NICU, Gauhati Medical College and Hospital, Guwahati, Assam. The study included 94 culture positive neonatal sepsis admitted to the above centre from 1st June, 2021 to 31st May, 2022. Result: Out of 1120 cases, 94 culture positive cases were taken in the study of which 87% had high CRP, 75.5% neonates had thrombocytopenia, 65.9% had high mean platelet volume and 40.4% with high platelet distribution width.CRP had significant correlation with MPV and PDW with p-values of 0.023822 and 0.011713 respectively but not with plateletcrit. A high MPV of 10.6% in gram positive sepsis cases, 30.8 % gram negative and 24.5% in fungal sepsis cases. Conclusion: Platelets and its indices can be considered as a diagnostic tool for neonatal sepsis as it is cheap, rapid, and easily available and does not require additional equipment.